2020
DOI: 10.1101/2020.01.21.20018101
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comprehensive assessment of PINK1 variants in Parkinson’s disease

Abstract: Multiple genes have been associated with monogenic Parkinson's disease and Parkinsonism syndromes. Mutations in PINK1 (PARK6) have been shown to result in autosomal recessive early onset Parkinson's disease. In the past decade, several studies have suggested that carrying a single heterozygous PINK1 mutation is associated with increased risk for Parkinson's disease. Here we comprehensively assess the role of PINK1 variants in Parkinson's disease susceptibility using several large datasets totalling 376,558 ind… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…7,8 However, the possible role of monoallelic pathogenic PINK1 and PRKN mutations in Parkinson's disease remains a matter of vivid debate: a recent study found 0.089% of monoallelic PINK1 mutation carriers in cases compared to 0.071% in controls in a large population screen (n=376,558). 9 Another study did not find any associations between PRKN variants and risk of Parkinson's disease. Pathogenic and likely-pathogenic heterozygous single nucleotide variants and copy-number variations were less frequent in Parkinson's disease patients (1.52%) compared to controls (1.8%).…”
Section: Introductionmentioning
confidence: 96%
“…7,8 However, the possible role of monoallelic pathogenic PINK1 and PRKN mutations in Parkinson's disease remains a matter of vivid debate: a recent study found 0.089% of monoallelic PINK1 mutation carriers in cases compared to 0.071% in controls in a large population screen (n=376,558). 9 Another study did not find any associations between PRKN variants and risk of Parkinson's disease. Pathogenic and likely-pathogenic heterozygous single nucleotide variants and copy-number variations were less frequent in Parkinson's disease patients (1.52%) compared to controls (1.8%).…”
Section: Introductionmentioning
confidence: 96%
“…In order to examine the genetic basis of iRBD and its conversion, recent studies have examined whether PD-or DLB-associated genes are also associated with iRBD and whether they affect its conversion. It was demonstrated that while some genes such as GBA (Krohn et al, 2019b), TMEM175 (Krohn et al, 2019a) and SNCA (Krohn et al, 2019c) are associated with iRBD, other PD and DLB genes such as LRRK2 (Ouled Amar Bencheikh et al, 2018), APOE (Gan-Or et al, 2017) and MAPT (Li et al, 2018) are not. However, the association between SMPD1 and iRBD has not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…In order to examine the genetic basis of iRBD and its conversion, recent studies have examined whether PD-or DLB-associated genes are also associated with iRBD and whether they affect its conversion. It was demonstrated that while some genes such as GBA (Krohn et al, 2019b), TMEM175 (Krohn et al, 2019a) and SNCA (Krohn et al, 2019c) are associated with iRBD, other PD and DLB genes such as LRRK2 (Ouled Amar Bencheikh et al, 2018), APOE (Gan-Or et al, 2017) and MAPT (Li et al, 2018) are not. However, the association between SMPD1 and iRBD has not been investigated.…”
Section: Introductionmentioning
confidence: 99%